Pelatihan Pembuatan Pupuk Organik Cair Berbahan Dasar Limbah Organik Rumah Tangga di Kelurahan Bello - Santrum, Mario Justinianus; Tokan, Moses Kopong; Taek, Paulus; Nikmah, Nikmah; Imakulata, Mbing Maria (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
Garbage is still a problem in almost all regions in Indonesia, including in the Bello Sub-district of Kupang City of East Nusa Tenggara. Garbage in Bello Sub-district, some are simply thrown on the side of the road and some are collected to be disposed of individually or per household to landfills. In fact, with the right and simple technology, waste that used to be a problem as waste, dirty, smelly, causing disease and polluting the environment can become goods that can be utilized and have economic value. The purpose of this community service activity is to provide a little scientific knowledge to the public about the benefits of household organic waste and involve the community in making liquid organic fertilizer (LOF). The methods used were lectures and question-and-answer discussions during counseling about the benefits of household organic waste and liquid organic fertilizer for plant growth and production as well as soil fertility, and demonstrations during the manufacture of liquid organic fertilizer. The results of community service activities at RT 02/RW 01 of Bello Sub-district, obtained 1 training community group consisting of 10 housewives, whose were enthusiastic in participating in this training activity as shown by their full attention to the counseling activities provided by the presenters and demonstration activities for making liquid organic fertilizer by demonstrators, and also by their presence which is always complete, both at the first meeting (opening and demonstration of making LOF) on 8 July 2023 and at the second meeting (observation of results and closing) on ​​30 July 2023. In addition, from this community service activity, around 22 liters of LOF were also produced which were then distributed to each member of the training community group, each member of the activity implementation team who was present, and two facilitators for making LOF.